2021
DOI: 10.4236/jss.2021.95033
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Research on Mental Health Problems of Poor College Students in Old Revolutionary Areas

Abstract: In August 2015, General Secretary Xi Jinping stressed at the National Hygiene and Health Conference that "we should increase basic research on mental health issues, do a good job in popularizing knowledge about mental health and diseases, and standardize the development of mental health services such as psychological treatment, counseling and so on". Lead "little bees" team to visit poor students and collect their information, giving follow-up and one-on-one support to them four years in a row, adopting releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…e main control chip (MCU) is the core of the risk assessment system for students' mental health crisis counseling, which is equivalent to the human brain [10], it controls the entire risk assessment system, mainly converting the collected analog signals into data signals without interruption, the collected data signals are digitally filtered and transmitted [3]. MCU has the advantages of small size and low power consumption, it can use one or more USART communication interfaces carried by itself, and the high-frequency processing speed is used to collect and digitally filter the signal, which reduces the configuration of the underlying registers to a certain extent [11]. MCU has multiple built-in A/D converters, which use a higher clock frequency to convert analog signals with a resolution greater than 16 bits into data signals, and can complete the corresponding functions through fewer peripheral circuits, reduce the possibility of problems during transmission, and improve the stability of performance.…”
Section: Selection Of Main Control Chipmentioning
confidence: 99%
“…e main control chip (MCU) is the core of the risk assessment system for students' mental health crisis counseling, which is equivalent to the human brain [10], it controls the entire risk assessment system, mainly converting the collected analog signals into data signals without interruption, the collected data signals are digitally filtered and transmitted [3]. MCU has the advantages of small size and low power consumption, it can use one or more USART communication interfaces carried by itself, and the high-frequency processing speed is used to collect and digitally filter the signal, which reduces the configuration of the underlying registers to a certain extent [11]. MCU has multiple built-in A/D converters, which use a higher clock frequency to convert analog signals with a resolution greater than 16 bits into data signals, and can complete the corresponding functions through fewer peripheral circuits, reduce the possibility of problems during transmission, and improve the stability of performance.…”
Section: Selection Of Main Control Chipmentioning
confidence: 99%
“…If college students can have more psychological capital, possess optimistic and confident psychological quality, and be full of hope for the future, they can deal with various problems better in life. In this way, in the development of his or her career ( Figure 3 ), he or she can “respond to all changes with the same changes,” which will benefit him or her immensely [ 9 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the mental health problems of economically disadvantaged college students are not effectively addressed in the short term. Through a survey of economically disadvantaged college students in old revolutionary areas, a study found that, due to family economic situations, economically disadvantaged college students were unable to meet their most basic survival needs, felt inferior, and became lonely, apathetic, and anxious [ 2 ].…”
Section: Introductionmentioning
confidence: 99%